التحكيم لحل النزاعات في العقود الادارية الدولية - السامرائي, نهاد عبد اللطيف (Tasnim International Journal for Human, Social and Legal Sciences, 2023)
The topic of referring to arbitration as a mean to solve conflicts in international administrative contracts، is a modern topic، which legislator،judiciary and administrative jurisprudence began to pay attention to it all over the world، which arbitration is not confined to civil and international trade conflicts، but it has expanded to include new areas as the case in administrative conflicts which the state or one of the public law people is a party، as a public authority.Jurist and jurisprudence differed on the possibility of resolving international administrative conflicts thought arbitration.Administrative arbitration is a procedure related an administrative dispute where one party is an administrative contact acts as a public authority and it is related to an administrative contract، so we find that the clauses of the administrative arbitration are an administrative contract where one party is a public authority.We find that most countries of different legal systems have adopted arbitration in general and administrative arbitration in particular and that where it is considered as an important tool for adjudication of disputes arising from administrative contracts with private law، the task of arbitration is assigned to members have nothing to do with judiciary and who are called (arbitrators) being chosen by the parties of the conflict.The administrative arbitration is distinguished from other similar systems in the fact that it ends with an effective arbitrary decision that is not subject to the control of any other authority while we find that reconciliation is a contract where a potential conflict between two parties is resolved where each party waives of part of his claim so that the reconciliation is done a contractual action whereas arbitration is resolved by a judicial action.The researcher concluded with the most important results، the most important of which is that the arbitration contract is one of the consensual contracts in which the parties have the right to waive recourse to the judiciary until reaching a positive or negative settlement of the dispute.Arbitration is the most acceptable method locally and internationally.As for their most important recommendations، they are confined to the necessity of forming a special department for arbitration، in the ministries and government agencies affiliated with them، and one of its tasks will be amicable settlement between the parties to the dispute، with the need to stipulate the jurisdiction of the Administrative Court to consider arbitration of administrative disputes.